Plant Stress Responses: Molecular Mechanisms and Ecological Impact - Yazdani, Sahar; Karimi, Reza; Al-Mousawi, Zainab (Research of Scientia Naturalis, 2025)
Plant stress responses play a crucial role in determining plant survival and productivity under various environmental conditions. Stress factors such as drought, extreme temperatures, and pathogen attacks can significantly affect plant growth, metabolism, and overall ecosystem balance. Despite extensive research on individual stress mechanisms, a comprehensive understanding of the molecular pathways that mediate these responses remains limited. This study aims to investigate the molecular mechanisms underlying plant stress responses and their broader ecological impact, focusing on how plants adapt to multiple stressors simultaneously. A combination of laboratory experiments and field observations was employed to examine gene expression, protein synthesis, and physiological changes in plants exposed to stress. Molecular techniques such as RNA sequencing, protein assays, and enzyme activity analysis were used to identify key genes and proteins involved in stress responses. Results reveal that plants activate complex signaling networks involving hormones like abscisic acid, salicylic acid, and ethylene to manage stress. Specific genes, such as DREB and NAC families, are upregulated to enhance tolerance, while antioxidant enzymes play a significant role in mitigating oxidative damage. These responses contribute to improved plant resilience and stability within ecosystems. The study concludes that understanding the molecular mechanisms of plant stress responses is essential for developing strategies to enhance crop resilience and ecological sustainability.